Factors Influencing Customers’ Interest at Alam Sutera Mall, Indonesia - Maria, Hesti; Putri, Indah Wira; Bernarto, Innocentius; Meilani, Yohana F. Cahya Palupi (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
This study aims to determine factors attracting customers to a shopping mall, especially the potential customers to AlamSutera Mall. It was done in a quantitative manner, empirically testing a conceptual model consisting of convenience, tenant variants, internal environment, leisure mix and promotions as the variables. The data were analyzed through structural equation modelling (SEM) on a sample of 105 visitors. The results showed that the convenience and leisure mix had a positive influence on frequency of visits, and the frequency of visits had a positive influence on purchase intention. However, the tenant variant, promotions and internal environment in the shopping mall did not have a positive influence on the frequency of visits. This study provides input to shopping mall managers to understand how to attract potential customers.